Mathematical Formula to Determine Geometrical Dimensions of Electrode Metal Droplets Transferred with Short Circuits - Ilyashchenko D. P. Dmitry Pavlovich; Chinakhov D. A. Dmitriy Anatol'evich; Kirichenko K. Yu.; Sydorets V. N. (2018, 2018)
Title screen